Engineering Calculation of Fracture Toughness of Materials with Chevron-Notched Specimens; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Deryugin Ye. Yevgeny; Panin V. E. Viktor Evgenyevich; Suvorov B. Boris; Kibitkin V. Vladimir; Antipina N. A. Nataljya Alekseevna (2015, 2015)
Title screen